2009
DOI: 10.1021/jp906483z
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effect of Hydrogen-Bonded Chains in the Environment of a π → π* Chromophore

Abstract: Laser resonant two-photon ionization UV spectra provide clear evidence that the effect of increasing the length of the hydrogen-bonded chain consisting of molecules such as NH 3 , H 2 O, or CH 3 OH on the π f π* excitations of cis-7-hydroxyquinoline (cis-7HQ) is strongly cooperative [Thut; et al. J. Phys. Chem. A 2008, 112, 5566.] A theoretical analysis of the experimental data is provided to identify the origin of this cooperativity for four chains. The computational method to determine the changes of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…5, and alternatively known as the "neglect of di↵erential response of the environment" (NDRE) approximation. 10 For the calculations with reconstructed potentials, the terms in the exchange-correlation-kinetic-energy kernel are approximately evaluated with the electron densities of the isolated subsystems. Tests without the embedding contribution in the exchange-correlation kernel confirm that these contributions are very small, even at the shortest distances considered here.…”
Section: Methodsmentioning
confidence: 99%
“…5, and alternatively known as the "neglect of di↵erential response of the environment" (NDRE) approximation. 10 For the calculations with reconstructed potentials, the terms in the exchange-correlation-kinetic-energy kernel are approximately evaluated with the electron densities of the isolated subsystems. Tests without the embedding contribution in the exchange-correlation kernel confirm that these contributions are very small, even at the shortest distances considered here.…”
Section: Methodsmentioning
confidence: 99%
“…Shortly after, Wesołowski implemented a simplified version of this subsystem‐based response theory, in which it is explicitly assumed that the response contribution from the environment (subsystem B ) is zero . This case, later called “uncoupled FDE” (FDEu) or “neglect of dynamic response of the environment” (NDRE), may be regarded as a strict FDE‐TDDFT variant, in which the environmental density is considered frozen also in the response framework. The corresponding response equation looks like that of the isolated system A , only that the orbitals and orbital energies are obtained under the influence of the effective embedding potential given in Eq.…”
Section: Property and Spectra Calculationsmentioning
confidence: 99%
“…Several studies investigated hydrogen‐bond–induced shifts in excitation energies. Fradelos et al demonstrated that the effect of an increasing number of solvent molecules in microsolvated cis ‐7‐hydroxyquinoline is highly non‐additive . For the same chromophore, it was later shown that solvatochromic shifts induced by hydrogen bonds are actually better described by FDEu than by supermolecular TDDFT calculations, taking equation‐of‐motion coupled cluster (EOM‐CC) calculations as a reference .…”
Section: Property and Spectra Calculationsmentioning
confidence: 99%
“…The geometries of the considered ''microsolvated'' cis-7-hydroxyquinoline clusters are also taken from Refs. [47,87].…”
Section: Cis-7-hydroxyquinoline In Hydrogen-bonded Complexesmentioning
confidence: 99%
“…The geometries of these complexes are taken from Refs. [47,87], which provide also reference benchmark shifts from EOM-CC and FDET calculations. The chosen systems represent well the worst scenario as far as the approximation introduced in Eq.…”
Section: Superposition Of Molecular Densitiesmentioning
confidence: 99%